Forensic Science Integration in Legal Education: a Paradigm Shift for Strengthening Legal Expertise in Pakistan - Ali, Muhammad Imran (Journal of Legal Studies, 2023)
The objective and scientific interpretation of evidence provided by forensic science is a crucial component of the contemporary judicial system. In Pakistan, forensic science education is not a part of the required curriculum for obtaining a Bachelor of Law (LL.B.) degree. Lawyer’s knowledge of the scope and limits of forensic research is hindered by the absence of a thorough forensic science component within law school. This, in turn, may obstruct the proper use of forensics in court procedures, which can slow down the distribution of justice. Forensic science education offers numerous benefits, including a holistic understanding of law and forensic science, interdisciplinary skills development, enhanced collaboration between lawyers and experts, and the development of specialized lawyers for handling complex cases. Law students may benefit from a deeper grasp of the scientific processes involved in criminal investigation, evidence collecting, preservation, analysis, and presentation by taking forensic science courses. Future lawyers will benefit from this understanding while trying cases, challenging expert testimony, and arguing on behalf of their clients. This article addresses the advantages, problems, and possible tactics for integrating forensic science into the LL.B. curriculum in Pakistan.